Efeitos da corrente interferencial sobre variáveis cardiovasculares em voluntários normotensos - Oliveira, Murilo Rezende (2018)
The autonomic nervous system (ANS) acts on modulation of the cardiovascular system and blood pressure (BP). The effects of electrotherapy on the cardiovascular system have been widely studied. Among the currents of sensorial electrical stimulation, Transcutaneous electrical nerve stimulation (TENS) has presented favorable results when applied to the starred ganglia, since it alters the autonomic balance and depending of the parameters, favoring the reduction of BP in normotensive and hypertensive volunteers. Another form of sensory stimulation is the interferential current (IC), but its effects on the cardiovascular system have been little studied. This electrical current presents special characteristics in relation to TENS, because due to its lower impedance, it can generate deeper effects in the tissues, which could present more pronounced results on cardiovascular system. The aim of the present study is to evaluate the effects of the application of IC with different amplitude-modulated frequency (AMF) (100Hz and 10Hz) on the autonomic balance and BP of healthy volunteers. A randomized, double-blind, crossover clinical trial was performed. The sample consisted of 30 healthy volunteers of both sexes (21 women) with a mean age of 23.7 ± 2.7 years and a body mass index (BMI) of 23.2 ± 2.7 kg/m². The volunteers were submitted to the placebo intervention, IC with AMF 100Hz and CI with AMF 10Hz applied in the paravertebral ganglion region for 30 minutes. All interventions and evaluations were performed with interval of one week. The autonomic balance was evaluated by the technique of heart rate variability (HRV) and the signals captured by frequency meter (Polar 810i). The BP measurements were measured using a multiparameter monitor (Dixtal, model 2021). Evaluations were performed before and immediately after the interventions. The research showed that IC modified the autonomic balance, where AMF 10Hz decreased sympathetic activity and increased parasympathetic activity, while the AMF 100Hz presented opposite results. BP did not change over the course of the study. These results suggest that AMF 10Hz presents a therapeutic potential in the nonpharmacological management of hypertension.